Effect of Stimulus Polarity on Speech Evoked Auditory Brainstem Response - Kumar, Kaushlendra (Audiol Res, 2014)
The aim of the present study was to investigate the effect of stimulus polarity on speech evoked auditory brainstem response (ABR). In order to accomplish it, speech evoked ABR was recorded with various stimulus polarities from 17 normally hearing adults. The result of the study shows differential effect of stimulus polarity on components of speech evoked ABR. Latency of peaks for onset, sustained and offset responses of speech evoked ABR were found to be not significantly different across stimulus polarities. In contrast, the amplitude of first formant and high frequency components was found to be significantly reduced for alternating polarity compared to single polarity, while amplitude of fundamental frequency response was not affected by polarity of the stimuli. Thus speech evoked ABR may be recorded using single polarity rather than using alternating polarities.